1995
DOI: 10.1210/jcem.80.8.7629228
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin increases markers of osteogenesis for the human species in vitro and in vivo.

Abstract: Phenytoin therapy is a well recognized cause of gingival hyperplasia, a condition characterized by increased gingival collagen synthesis, and may also cause acromegalic-like facial features. Based on these clinical findings suggestive of anabolic actions, we sought to test the hypothesis that phenytoin acts on normal bone cells to induce osteogenic effects. To test the direct actions of phenytoin on human bone cells, we measured the dose responses to phenytoin for [3H]thymidine incorporation, cell number, alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…Moreover, recent in vitro studies have shown that AEDs directly stimulate osteoblast activity. 19 Thus, it is possible that the younger male skeleton with enhanced bone turnover from AED therapy may require a substantially higher calcium intake to adequately suppress bone resorption and optimize bone mineralization. Alternatively, the AED effect may involve the same mechanism that causes agerelated bone loss that could accelerate this process in younger patients.…”
Section: Commentmentioning
confidence: 99%
“…Moreover, recent in vitro studies have shown that AEDs directly stimulate osteoblast activity. 19 Thus, it is possible that the younger male skeleton with enhanced bone turnover from AED therapy may require a substantially higher calcium intake to adequately suppress bone resorption and optimize bone mineralization. Alternatively, the AED effect may involve the same mechanism that causes agerelated bone loss that could accelerate this process in younger patients.…”
Section: Commentmentioning
confidence: 99%
“…The pharmacological effect of phenytoin is achieved by blocking sodium and calcium ion channels in neurons (Tunnicliff, ; Shaw et al ., ), which reduces neurotransmitter release, tetanic postsynaptic potentiation and neuronal firing rate (Kaindl et al ., ). One of the side‐effects of phenytoin medication is the abnormal cellular growth (hyperplasia) of several tissues, such as oral mucosa (Sano et al ., ), bone (Lau et al ., ), heart (Zhou et al ., ) and skin (Shaw et al ., ). Additionally, topical phenytoin administration promotes cutaneous wound healing by stimulating proliferation of granular tissue (Shaw et al ., ) and increasing connective tissue growth factor (Kantarci et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that bone alkaline phosphatase (ALP) isoenzyme activity, a marker of bone formation, was substantially increased in phenytoin-treated patients (Hahn and Avioli, 1975). We recently presented preliminary evidence that epileptic patients with long-term use of phenytoin exhibited significantly higher serum levels of osteocalcin, a serum marker for bone formation (Brown et al, 1984), than did age-matched patients (Lau et al, 1994). Furthermore, patients on anti-epileptic drugs showed significantly higher serum levels of several biochemical bone formation markers (skeletal ALP, osteocalcin, and the Cterminal extension peptide of type I procollagen) than did control subjects (Valimaki et al, 1994).…”
Section: Introductionmentioning
confidence: 99%